Clinical Characteristics of COVID-19 in Neonates and Infants Younger Than 3 Months - Fatemeh Varshoei; Mohammad Sadegh Rezai; Roya Farhadi; Azin Hajialibeig; Saeid Mohammadi; Masoud Moradi; Fatemeh Hosseinzadeh (Journal of Pediatrics Review)
Background: COVID-19 is a respiratory infection that appeared as a pandemic affecting children and adults in China in 2019. Objectives: To better understand COVID-19 in young children, we evaluated the epidemiological, clinical, and outcomes of SARS-CoV-2 infection in neonates and 1-3 months old infants and compared the differences between the two groups. Methods: This retrospective analysis included children with a COVID-19 diagnosis admitted to Bouali and Imam Khomeini tertiary hospitals in Sari City, Iran, between March 2019 and March 2022. Demographic data such as age, sex, comorbidity, clinical characteristics and symptoms, medications, and laboratory test results were extracted from the patient’s medical records. Statistical analysis was performed using SPSS software, version 22, and P<0.05 were considered statistically significant. Results: This study evaluated 152 children, including 34 neonates (22.4%) and 118 infants (77.6%), with a median age of 49.5 [interquartile range (IQR): 33-66] days. The frequencies of mild, moderate, and severe/multisystem inflammatory system in children (MIS-C) cases were 96(63.2%), 29(19.1%), and 27(17.8%), respectively (P=0.879). Overall, 90 patients (59.2%) were boys, and 62(40.8%) were girls (P=0.695). COVID-19 reverse transcription-polymerase chain reaction (RT-PCR) test was positive in 65 children (42.8%) (P=0.022), and 3 (2%) expired. Fever was the most common symptom (75%), followed by cough (56.6%), poor feeding (46.1%), dyspnea (32.9%), and lethargy (32.2%). Twenty-nine patients (19.1%) required intensive care unit (ICU) admission, and 6(3.9%) underwent mechanical ventilation (P=0.463 and P=0.126, respectively). The median duration of hospital stay was 5 days (IQR: 4-7 days). The median duration of antibiotic therapy did not differ among the groups (P=0.786). Sepsis workup was performed in 82.9% of patients, and none had a positive cerebrospinal fluid culture. Conclusions: Although this study showed a 5% vertical transmission rate, only delivery from a mother with COVID-19 or having a positive COVID-19 reverse transcription polymerase chain reaction (RT-PCR) test result without symptoms is not a reason for a sepsis workup. Moreover, in infants under 3 months who are hospitalized due to confirmed COVID-19 and do not have sepsis symptoms, there is no indication of a lumbar puncture (LP) procedure.